Characterization And Testing Of PIV Illumination System Using High Power Led On Naca 0018 Airfoil At Low Reynolds Number - Lai, Hoong Chuin (2018)
This thesis reports the work on characterization and evaluation of the particle image velocimetry (PIV) illumination system using high power light emitting diode (HPLED). An illumination system using these HPLEDs was developed with the custom-built driver circuit. The driver circuit and the HPLEDs were characterized. As a result, input transistor-transistor logic (TTL) signal and the metal oxide semiconductor field effect transistor (MOSFET) output signal for the driver circuit were compared while emitted wavelength by the HPLEDs at different power levels and pulsing frequencies were measured. The HPLEDs emitted light with wavelength that is located at the peak of the spectral sensitivity of the imaging device. The light intensity emitted by the HPLED is also found to be increasing linearly together with the power supplied. The evaluation of the developed illumination system was performed by investigating the case study of flow field across the impulsively started NACA 0018 airfoil in a water tank. The airfoil was set at various angles of attack ranging from 0°to 45°with intervals of 5°, with both flow Reynolds numbers of 6740 and 9235. Qualitative and quantitative comparisons were made on images acquired by both illumination systems. Lift force generated were also measured at the same time to justify the results obtained from the flow measurement. Images acquired were analyzed using PIVLab, a MATLAB based PIV correlation software. Both flow fields for steady and unsteady cases were successfully investigated. Through the case studied, the advantages and limitations of the developed illumination system could be determined. It showed that HPLEDs promises several advantages in terms of cost, safety and performance. Similar performance to the laser illumination system can be achieved but only requires 10% of its cost by using the HPLEDs illumination system. It has a high potential to be developed into an alternative to replace the laser-based illumination system for PIV in the near future.